Command authority - Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2013)
"The #1 New York Times-bestselling author and master of the technothriller returns with his All-Star team. There's a new strong man in Russia but his rise to power is based on a dark secret hidden decades in the past. The solution to that mystery lies with a most unexpected source, President Jack Ryan"--